Keterampilan Menganyam Noken Sebagai Upaya Melestarikan Budaya Papua - Helena Grace Binu; Maya Lagu; Selvinus Iyai; Servinus Bria; Ovelita Yadantrar; Susana Magdalena Welly Muskita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Noken is a traditional bag made from woven or knitted plant fibers. Noken, as a native Papuan culture that has received recognition from UNESCO, is a native Papuan handicraft whose sustainability needs to be taken into account. Protection for Papuan noken is a form of preserving the community of its heirs in maintaining the level of extinction and becoming a bond between themselves and their natural life. The method used is qualitative with the data collection technique being library research, where the author examines several library sources as references in this writing. Preserving noken is not only important to maintain the continuity of Papuan culture, but also as an effort to unify the culture between more than 250 ethnic groups in Papua.